2018
DOI: 10.1007/s11356-018-2728-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of seafood contamination under the marine strategy framework directive: contributions of the German environmental specimen bank

Abstract: Descriptor 9 (D9) of the European Union Marine Strategy Framework Directive refers to the compliance of contaminant levels in fish and other seafood of a defined marine region or subregion with human health threshold values. This requires georeferenced samples that are often difficult to obtain when relying on commercial fisheries or programs designed for monitoring human exposure. The present study examines whether georeferenced samples of blue mussel (Mytilus edulis) and eelpout (Zoarces viviparus) fillet of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The primary focus of the recently published occurrence data was on fish and marine sea food. As already indicated in the previous Opinion, α‐HBCDD prevailed in most studies and the median levels, especially in fish caught for consumption was generally below 1 μg/kg ww (Munschy et al., 2013, 2015; Kuc et al., 2014; Aznar‐Alemany et al., 2017; Fliedner et al., 2018; Malysheva et al., 2018; Nøstbakken et al., 2018; Vénisseau et al., 2018). However, a number of samples were detected where γ‐HBCDD was the dominating stereoisomer.…”
Section: Assessmentmentioning
confidence: 75%
See 1 more Smart Citation
“…The primary focus of the recently published occurrence data was on fish and marine sea food. As already indicated in the previous Opinion, α‐HBCDD prevailed in most studies and the median levels, especially in fish caught for consumption was generally below 1 μg/kg ww (Munschy et al., 2013, 2015; Kuc et al., 2014; Aznar‐Alemany et al., 2017; Fliedner et al., 2018; Malysheva et al., 2018; Nøstbakken et al., 2018; Vénisseau et al., 2018). However, a number of samples were detected where γ‐HBCDD was the dominating stereoisomer.…”
Section: Assessmentmentioning
confidence: 75%
“…The authors suggested that this finding related to new sources of emissions of BFRs. The same authors analysed georeferenced samples of eelpout ( Zoarces viviparus ) fillet from the German environmental specimen bank for HBCDDs (Fliedner et al., 2018). Two sampling sites were located at German coastal areas of the Central North Sea and one site in the Bodden National Park of Western Pomerania.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring program, such as the German ESB, which have analyzed and archived annual pool samples (each consisting of several monthly samples) over a longer period of time, are not recommended to reduce the annual sampling frequency as this may disrupt the already existing long time series. Moreover, it is currently discussed that marine samples of the ESB may be used also in the context of Descriptor 9 of the Marine Strategy Framework Directive [57,58]. This would require the best possible knowledge of mussel contamination for compliance assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The North Sea sites are located in the National Parks and Biosphere Reserves 'Lower Saxony Wadden Sea' (site NS 1) and 'Schleswig-Holstein Wadden Sea' (NS 2), the Baltic Sea sites (site BS) are situated in the 'Bodden National Park of Western Pomerania' . More details including possible sources of contaminations at these sites are given in [38,39].…”
Section: Sampling Sitesmentioning
confidence: 99%